1998
DOI: 10.1007/s002340050645
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial vascular stenosis and occlusion: comparison of 3D time-of-flight and 3D phase-contrast MR angiography

Abstract: We compared the value of 3D time-of-flight (TOF) and phase-contrast (PC) MR angiography (MRA) for detection and grading of intracranial vascular steno-occlusive disease. Unenhanced 3D-TOF MRA and 3D-PC MRA (30-60 cm/s velocity encoding) were performed at the level of the circle of Willis in 18 patients, mean age 56 +/- 10 years. Postprocessed images using a maximum-intensity projection reconstruction with multiple targetted projections were analysed. A total of 126 vessels was assessed by PC MRA and 143 by TOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 16 publications
1
40
0
4
Order By: Relevance
“…For detecting high-grade stenosis, a recent study using 3T MRA showed a sensitivity of 78–85%, a specificity of 95%, a positive predictive value of 75–79%, and a negative predictive value of 95–97% [46]. For detecting 50–99% stenosis, previous studies using 1.5T MRA reported a sensitivity of 80–100% [19,47,48]. Another recent study using 1.5T MRA reported a sensitivity of 70% and a positive predictive value of 65% for detecting 30–99% stenosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…For detecting high-grade stenosis, a recent study using 3T MRA showed a sensitivity of 78–85%, a specificity of 95%, a positive predictive value of 75–79%, and a negative predictive value of 95–97% [46]. For detecting 50–99% stenosis, previous studies using 1.5T MRA reported a sensitivity of 80–100% [19,47,48]. Another recent study using 1.5T MRA reported a sensitivity of 70% and a positive predictive value of 65% for detecting 30–99% stenosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…The most common application of 3D TOF is intracranial angiography (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In particular, 3D TOF has been used for diagnostic imaging of intracranial occlusions (32,33) as well as aneurysms (34,35).…”
Section: Applicationsmentioning
confidence: 99%
“…In particular, 3D TOF has been used for diagnostic imaging of intracranial occlusions (32,33) as well as aneurysms (34,35). The high resolution of the 3D acquisition provides excellent depiction of small intracranial vessels.…”
Section: Applicationsmentioning
confidence: 99%
“…A spectral broadening with low-frequency parts in the spectra and harmonic vibrations of the vessel wall (musical murmurs) were noted and served as secondary criteria, interpreted only as vessel stenosis if they were associated with a segmental flow acceleration. 13 …”
Section: Partmentioning
confidence: 99%